1998
DOI: 10.1111/j.1445-2197.1998.tb04742.x
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Biliary Injury: More Than a Learning Curve Problem

Abstract: Background:The increase in the incidence of iatrogenic injury to the extrahepatic biliary tree that has been documented since the introduction of laparoscopic cholecystectomy (LC) has been explained as a 'learning curve' problem. The early New Zealand experience has been published and the present study was undertaken to determine whether there had been any change in the incidence, nature and management of laparoscopic biliary injuries (LBI) after further experience with LC. Methods: A nationwide audit was unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(41 citation statements)
references
References 16 publications
1
38
0
2
Order By: Relevance
“…3 Similarly, the results of a nationwide audit in New Zealand demonstrated that despite increasing experience with LC, the incidence of iatrogenic bile duct injury remained stable. 22 Therefore, we can assume that bile duct strictures and injuries will continue to be a problem well into the new millennium.…”
Section: Discussionmentioning
confidence: 99%
“…3 Similarly, the results of a nationwide audit in New Zealand demonstrated that despite increasing experience with LC, the incidence of iatrogenic bile duct injury remained stable. 22 Therefore, we can assume that bile duct strictures and injuries will continue to be a problem well into the new millennium.…”
Section: Discussionmentioning
confidence: 99%
“…Os principais motivos apontados para explicar a maior incidência destas lesões foram a presença de reação inflamatória intensa, variações anatômicas do pedículo biliar, sangramento durante a operação, uso indiscriminado do termocautério, a qualidade do equipamento e, a mais importante de todas, a inexperiência do cirurgião com o novo método [7][8][9] . Observou-se que, com o desenvolvimento da habilidade e ganho de experiência, estes índices tornavamse menores e comparáveis aos dos procedimentos chamados convencionais.…”
Section: Introdução Introdução Introdução Introdução Introduçãounclassified
“…Traditionally, surgeons opt for operations with lower complication rates, and the ''learning curve'' was one of the arguments to account for the increased incidence of BDIs during LC [12]. However, further publications have reported that this incidence remains higher even when ''learning curve'' is accounted for [4,13,14], even in light of technological advances that have improved visualization and instrumentation [14][15][16][17][18]. Despite this evidence, LC remains the treatment of choice for symptomatic gallstones, a fact most likely attributable to the benefits of less postoperative pain, shorter hospital stay, better cosmetic result, and increased patient satisfaction [12,[19][20][21][22].…”
mentioning
confidence: 99%